The hospital management practices in Chinese county hospitals and its association with quality of care, efficiency and finance - Yidan Zhu; Yifei Zhao; Lixia Dou; Ruya Guo; Xuefei Gu; Runlin Gao; Yangfeng Wu (BMC, 2021)
Abstract Background County hospitals as the backbone of the China's healthcare system are providing services for over 70% of the total population. However, the hospital management practice (HMP) and its links with quality of care, efficiency and finance in these hospitals are unknown. Methods We did two cross-sectional surveys of HMP in 2013 and 2015 among 101 county hospitals across rural China. Three managing roles (hospital director, director of medical affairs office and director of cardiology) and a cardiologist were invited to the surveys. A novel HMP rating scale, with 100 as full score, was used to measure the HMP in 17 indicators under four dimensions (target, operation, performance, and talent management) for each hospital. We analyzed the association of HMP score with variables on quality of care, efficiency and finance using linear mixed models with and without adjustment for potential confounders. Findings A total of 95 hospitals participated in at least one survey and were included in the analysis. The overall mean HMP score varied dramatically across the hospitals and 84% of them scored less than 60. The dimension mean HMP score was 38.6 (target), 56.4 (operation), 53.2 (performance) and 55.7 (talent), respectively. The pattern of indicator mean HMP score, however, was almost identical between hospitals with high and low overall HMP score, showing the same 'strength' (staff satisfaction, staff performance appraisal, 'hard wares', patient-centered services, etc.) and 'weakness' (target balance, target setting, continuous quality improvement, penalties on staff with dissatisfied performance, etc.). The associations of overall mean HMP score with quality of care and efficiency variables and cost per hospitalization was not statistically significant. The statistical significance in the association with hospital annual total income disappeared after adjusting for region, teaching status, number of competitors, number of staff and number of beds in use. Conclusion The HMP in Chinese county hospitals scores low in general and was not significantly associated with hospital care quality, efficiency and finance. The current healthcare reform in China should address the micro level issues in hospital management practices.